Pengaruh Keterikatan Konsumen Terhadap Media Sosial Instagram @maxxisid - Febri Rakhmawati Arsj (PUTRA JAWA PUBLISHER, 2025)
The development of adequate transport infrastructure improves mobility efficiency, enhancing product competitiveness and economic performance. Motorbikes, a practical alternative for addressing urban congestion, have become both a means of transport and a lifestyle symbol. Enthusiasts often discuss various motorbike-related topics, including tyres. Maxxis tyres, a popular brand, utilizes Instagram for customer engagement. This study aims to analyze the impact of Maxxis tyres' customer engagement on Instagram. Using a descriptive and quantitative approach, primary data was collected through a Google Form questionnaire from 100 motorbike owners who are active Instagram users. Data analysis involved validity and reliability tests, normality tests, linear regression, t-tests, and determination coefficient analysis. Results revealed that customer engagement significantly and positively influences Instagram as a social media platform, highlighting the effectiveness of Maxxis tyres' strategy in leveraging digital platforms to connect with consumers.